Survival Analysis of 121 Stage N2-IIIa Non-small Cell Lung Cancer Patients Treated with Surgery - Heli YANG; Liang DAI; Pei LI; Luyan SHEN; Wanpu YAN; Mengying FAN; Keneng CHEN (Chinese Journal of Lung Cancer, 2015)
Background and objective It has still been controversial to treat N2-IIIa non-small cell lung cancer (NSCLC) patients by surgery or non-surgery. We retrospectively analysed the survival of 121 stage N2-IIIa NSCLC patients treated with surgery and explored their postoperatively long-term prognostic factors. Methods All of 1,290 patients in Beijing Cancer Hospital underwent resection by single-surgeon-team, among which 121 cases with stage N2-IIIa were enrolled in the study. We retrospectively analysed the impact of gender, age, smoking, perioperative chemotherapy, incision, histological type, vascular tumor emboli, pTstage and tumor size on survival of stage N2-IIIa patients, and compared the survival between patients with single-and multi-station N2 metastasis, and between intraoperatively or postoperatively pathological N2 (IIIa1/a2) and preoperative N2 (IIIa3/a4). Univariate analysis was conducted by Kaplan-Meier curve, and significance test was performed by Log-rank test and Cox regression factor analysis was applicated for multivariate analysis. Results The 5-yr of all the 121 cases was 43.6%, with a median survival time being 50.3 mo. Univariate analysis showed the 5-year survival rate in patients with single- and multi- station N2 metastasis were 58.3% and 25.5%, respectively (P=0.001), 5-year survival rate in patients with stage IIIa1/a2 and stag IIIa3/a4 were 52.7% and 38.4%, respectively (P=0.020). Multivariate analysis demonstrated that only single station N2 (HR=0.326, 95%CI: 0.186-0.572, P<0.001) and IIIa1/a2 (HR=0.494, 95%CI: 0.259-0.941, P=0.032) were independent prognostic factors for stage N2-IIIa lung cancer patients. Conclusion The prognosis of stage N2-IIIa NSCLC patients with single-station N2 metastasis were better than those with multi-station N2 metastasis. Besides, IIIa1/a2 patients had a better survival compared with stage IIIa3/a4 patients. A multi-disciplinary comprehensive treatment based on surgery may allow patients with high selective stage N2-IIIa NSCLC to obtain a comparatively satisfying long-term survival.